Dynamics in Circulating Proinflammatory Biomarkers for Prognostic Assessment of Patients With Advanced HCC – A Substudy From the SORAMIC Trial - Schütte, Kerstin; Kupčinskas, Juozas; Morkunas, Egidijus; Öcal, Osman; Schinner, Regina; Seidensticker, Max; De Toni, Enrico N.; Ben Khaled, Najib; Pech, Maciej; Palmer, Daniel; Berg, Thomas; Sengel, Christian; et al. (Frontiers in Gastroenterology, 2022)
Introduction Prediction of response to treatment in patients with advanced hepatocellular carcinoma (HCC) may assist in selection of a personalized management. Objective This exploratory analysis of the palliative arm of the SORAMIC trial (ClinicalTrials.gov NCT01126645) evaluated the prognostic potential of basal and dynamic changes in systemic levels of interleukin 6 (IL-6), interleukin 8 (IL-8), systemic vascular endothelial growth factor (VEGF) and lipopolysaccharide (LPS). Methods We evaluated the correlations between overall survival (OS) and concentrations of IL-6, IL-8, VEGF and LPS at follow-up approximately 7-9 weeks after treatment initialization (FU) compared to baseline (BL) in 90 patients treated either with 90Yttrium (90Y) microspheres combined with sorafenib (n = 44) or with sorafenib (n = 46) alone. Results Changes in IL-6 concentration during treatment showed correlations with outcome. An increase in IL-6 concentration of less than 16.8 pg/mL over baseline readings was associated with better survival (median OS 16.3 months compared with 8.9 months (p = 0.0354)). Correlations with survival were not observed for VEGF or LPS concentrations at baseline, at FU or changes between these timepoints. Conclusions Changes of IL 6 serum levels at 7-9 weeks after treatment initialization but not of IL 8, VEGF and LPS add important information on outcome of advanced HCC patients treated palliatively within the SORAMIC trial.